Variabilidade espacial de atributos do solo em Sistema de terraços em região Semiárida - Lima, Luan Alves (2018)
Terraces are structures built along the terrain, constituted by a canal and a ridge, with the finality of to segment the length of the hillsides in order to intercept the runoff and soil transported by water erosion. Together with the intercepted soil by the terraces, there is also organic material and inputs which has been applied in the terraced agricultural area. In this sense, it was based the hypothesis that, there is spatial variability of the physical and chemical attributes of the soil with the practice of the terraces: as the terraces canals approaches, there is greater availability of nutrients, higher levels of organic matter and fine particles, improving fertility attributes and soil quality. The objective of this work was to verify the spatial variability of soil chemical and physical attributes, through the descriptive and geostatistical analysis in an area between terraces in the semi-arid region. The research was carried out in Iguaçu (Canindé - CE), in a terraced area eleven years ago, in the Cangati river basin. A regular sampling of the grid type was performed at 100 points, with 10 points spaced every 2 meters in width and every 5 meters in length, in an area 810 m2 between two terraces. After identification and georeferencing, the soil samples were collected in the layers of 0.0 to 0.10 m and 0.10 to 0, 20 m and taken to the UFC for the physical and chemical analyzes. The following physical attributes were quantified: granulometry with sand fractionation, clay dispersed in water (CDW) and calculated the degree of flocculation (DF). he chemical attributes evaluated were: hydrogenation potential (pH), electrical conductivity (EC), total nitrogen (NT) phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), sodium (Al), potential acidity (H + Al) and total organic carbon (TOC). The chemical attributes evaluated were: hydrogenation potential (pH), electrical conductivity (EC), total nitrogen (NT) phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), sodium (Al), potential acidity (H + Al) and total organic carbon (TOC) The chemical attributes evaluated were: hydrogenation potential (pH), electrical conductivity (EC), total nitrogen (NT) phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), sodium (Al), potential acidity (H + Al) and total organic carbon (TOC). Data were submitted to descriptive analysis followed by geostatistical analysis. In the geostatistics, the analysis of spatial dependence was verified, verified by the best adjustment of semivariograms followed by interpolation by ordinary kriging using GS+ Software. The physical attributes of the soil presented smaller variation of the data when compared to the chemical ones. Spatial dependence was classified as medium and strong in the physical and chemical attributes studied, with spatial dependence being more evident with increasing soil depth. There were higher clay contents and flocculation degree at points close to the terrace channel. The random arrangement of organic matter between the terraces allows one to reject the hypothesis of higher values found as it approaches the canals of the terraces. On the other hand, the hypothesis of higher content of fine particles (clay and DF) and availability of nutrients (V% and P) located near the terrace canal, improving fertility and soil quality, is accepted. The spatial variability of the attributes related to the granulometric fractions and potential acidity (H + Al), verified by the use of geostatistics in the area between terraces, shows the importance of the directed management, in order to guarantee the quality of soil and agricultural crops in terraced areas in the semiarid.